Molecular mechanisms of dragon’s blood in treating ulcerative colitis based on NF-κb/NLPR3/Caspase-1 pyroptosis signaling pathway - Bilian Cai; Xiaohua Qin; Xiaogang Huang; Xiaojin He; Huanying Zhong; Yuan Yu; Jinzhu Cui; Yilei Wen (PLoS ONE, 2025)
Objective To elucidate the molecular mechanism of dragon’s blood (DB) in the treatment of ulcerative colitis (UC). Methods Bioactive metabolites of DB absorbed into the bloodstream were characterized via LC-MS. Network pharmacology and molecular docking were employed to construct a target-pathway interaction model predicting DB’s therapeutic mechanism in UC. A 4% DSS-induced UC mouse model was used for experimental validation. Results DB markedly alleviated colonic injury in DSS-induced UC. A total of 255 active compounds were identified, including 6,4’-Dimethoxy-7-hydroxyisoflavone, 7-hydroxy-2-(4-methoxyphenyl) chromen-4-one, and Apigenin. Key molecular targets included NLPR3, MAPK1, TP53, HIF1A, and PTGS2. The NF-κB/NLPR3/Caspase-1 axis was implicated as a central pathway mediating the therapeutic effects of DB. Conclusion DB acts through a multi-component, multi-target, and multi-pathway strategy. Inhibiting the NF-κB/NLPR3/Caspase-1 pyroptosis pathway positions NLPR3 as a viable target for DB in UC intervention.